Avaliação Laboratorial e molecular de concentrado de hemácias devolvidas à fundação hospitalar de hematologia e hemoterapia do Amazonas - Nascimento, Marcelo Reis do (2017)
INTRODUCTION: The Hospital Foundation of Hematology and Hemotherapy of Amazonas - HEMOAM- collects approximately 60,000 blood bags a year with which it supplies the entire State of Amazonas. The packed red blood cell (CH) bag is the most widely used blood component in the world. Depending on the anticoagulant and additive solution, it is valid for up to 42 days when stored at 4 ± 2oC. However, erythrocytes continue their metabolism slowly, suffering in this adverse environment, damage to their morphology and energy production, which can trigger the Cell Injury process.OBJECTIVE: To analyze biochemical, hematological and molecular data on alternate days (7 to 7 days) in an attempt to verify indicative changes to increase oxidative stress in bags donated and returned to FHEMAOM.RESULTS: Of the 60 bags analyzed, 48 (80%) were male. The average age of volunteers for males was 34 ± 11.35 and 32 ± 10.23 years for females. The most frequent blood group in both genders was the “O” RhD positive, above 48%. Although we did not find significant differences, the blood bags returned to the blood center have increased levels of oxidative stress and hemolysis markers, in addition to other variations in hematological and biochemical parameters compared to the bags that were stored in the blood center. As expected, hematological data, despite the slight decrease in values, significant differences were not demonstrated in the analyzes from the 1st to the 42nd day. Serum values ​​for glucose and sodium, showed a significant decrease (p <0.001; P = 0.023, respectively), while for sodium, magnesium and LDH, significant increase (p <0.017; p = 0.029; p <0.001, respectively). All markers for oxidative stress showed significant differences throughout each analysis, with an increase in oxidative capacity (ROS), lipid peroxidation / hemolysis (TBARS), while a decrease in antioxidant capacity (ABTS) (all with p <.001). CONCLUSION. The differences found in the parameters analyzed between the bags that remained in the blood center and those returned from other agencies can be explained by transport and / or packaging outside the ideal temperature, which resulted in an increase in erythrocyte lesions. Few variations were demonstrated with statistical significance between the first 14 days, perhaps indicating that the erythrocytes are able to mitigate the increase in oxidative stress in this period. In addition, we verified the increase in TBARS as a result of lipid peroxidation, being influenced by the presence of heterozygosity as the greatest association force for homozygotes in SNPs rs1695 (Ile105Val) and rs1871042 (442-16C> T) for the GSTP1 and SOD rs4880 ( Ala16Val). We believe that a better understanding of endogenous and exogenous factors that affect oxidative status in blood balls, including genetic factors, is important for understanding oxidation in blood storage in order to improve clinical outcomes in blood transfusions. Keywords: Oxidative stress, Superoxide dismutase; GSTP1 SNPs